How Do Student Prior Achievement and Homework Behaviors Relate to Perceived Parental Involvement in Homework? - Núñez, José C.; Epstein, Joyce L.; Suárez, Natalia; Rosário, Pedro; Vallejo, Guillermo; Valle, Antonio (Frontiers in Psychology, 2017)
This study investigated how students’ prior achievement is related to their homework behaviors (i.e., time spent on homework, homework time management, and amount of homework), and to their perceptions of parental involvement in homework (i.e., parental control and parental support). A total of 1250 secondary students from 7th to 10th grade participated in the study. Structural equation models were fitted to the data, compared, and a partial mediation model was chosen. The results indicated that students’ prior academic performance was significantly associated with both of the students’ homework variables, with direct and indirect results linking achievement and homework behaviors with perceived parental control and support behaviors about homework. Low-achieving students, in particular, perceived more parental control of homework in the secondary grades. These results, together with those of previous research, suggest a recursive relationship between secondary school students’ achievement and their perceptions of parental involvement in homework, which represents the process of student learning and family engagement over time. Study limitations and educational implications are discussed.